Antipyretic, anti-inflammatory and antibacterial effects of Datura innoxia leave hydroalcoholic extract in rabbits: Zahraa, M. Ayad and Duraid, A. Abbas - Ayad, Zahraa M. (The Iraqi Journal of Veterinary Medicine, 2022)
Datura innoxia was tested as a proposed formula at concentration of 3% that evaluated in-vivo by using 12 rabbits divided equally into 3 groups (plant extract ointment, Tetracycline ointment, Vaseline vehicle). By inducing four abraded skin wound on the back of each group of rabbits by using three special scalpel device, two of the wounds were infected artificially with 250×108 cfu pathogenic Staphylococcus aureus while other two wounds were not infected. Two abraded wounds were treated topically once daily and for two weeks with 3% D.innoxia ointment or 3% tetracycline ointment and one abraded wound was left not treated and the other one was applied with Vaseline as control. Antipyretic effect was also evaluated by taking rectal temperature each 2 days. The result showed the superiority of the extract formula in the therapy of induced skin infection with S.aureus over that of tetracycline ointment at same concentration (3%), since it showed better healing activity, more anti-inflammatory and also better antipyretic effects than tetracycline and control groups. This must be due to its good pharmaceutical content that posses analgesic, anti-inflammatory, antipyretic as well as antibacterial effect than tetracycline that contain only antibacterial activity.